Beverage consumption pattern and its association on weight status among school children in Kota Bharu - Roslan, Syaidatul Nadia (Universiti Sains Malaysia, 2013)
Beverages contribute an important part in the daily diet of children. Recently, sweetened beverage has been related with the increasing prevalence of obesity among children. However, the type and frequency of beverage consumption among school children in Kota Bharu is unknown. Hence, the aim of this study was to evaluate the beverage intake among school children and investigate the associations of beverage consumption and weight status in Standard 5 school children. This cross sectional study was done with a total of 196 subjects (52% male, 48% female) in 2 primary schools in Kubang Kerian area. Subjects were interviewed using a questionnaire which comprises of 24 hour dietary recall, Food Frequency Questionnaire (FFQ), and anthropometric data form. Body height and weight were measured in order to obtain Body Mass Index (BMI) for each subject. The results showed that 11.7 % were overweight (> 85th percentiles) and 14.3% were classified as obese (> 97th percentiles). However, bivariate analysis showed that beverage consumption (as indicated by total energy intake and energy from beverage) was not associated with weight status. In this study, females tend to have higher values of energy from the beverage compared with males with average 296 kcal per day. It was noted that most of the children choose tea (10.2%) as the main beverage while coffee (5.1%) ranks the least. Tea (10.3%), fruit juice (9.5%) and milk (9.4%) were the top three beverages among the female subjects whereas males tend to choose milk (10.4%), tea (10.1%) and isotonic drink (9.7%) as their main beverages. In conclusion, there was no association between the beverage consumption and weight status among school children in Kota Bharu.